University differences in the graduation of minorities in STEM fields: Evidence from California - Peter Arcidiacono; Esteban Aucejo; Vincent Joseph Hotz (Institute for the Study of Labor (IZA), 2013)
The low number of college graduates with science degrees - particularly among under-represented minorities - is of growing concern. We examine differences across universities in graduating students in different fields. Using student-level data on the University of California system during a period in which racial preferences were in place, we show significant sorting into majors based on academic preparation, with science majors at each campus having on average stronger credentials than their non-science counterparts. Students with relatively weaker academic preparation are significantly more likely to leave the sciences and take longer to graduate at each campus. We show the vast majority of minority students would be more likely to graduate with a science degree and graduate in less time had they attended a lower ranked university. Similar results do not apply for non-minority students.
Keywords: I23; I24; J15; 330; STEM majors; minorities; college graduation; Akademiker; Bildungsabschluss; Minderheit; Ethnische Gruppe; Hochschule; Vergleich; Kalifornien